1998
DOI: 10.1074/jbc.273.44.28721
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nicotine Treatment Up-regulates Human α3β2 but Not α3β4 Acetylcholine Receptors Stably Transfected in Human Embryonic Kidney Cells

Abstract: Human nicotinic acetylcholine receptor (AChR) subtypes ␣3␤2, ␣3␤2␣5, ␣3␤4, and ␣3␤4␣5 were stably expressed in cells derived from the human embryonic kidney cell line 293. ␣3␤4 AChRs were found in prominent 2-m patches on the cell surface, whereas most ␣3␤2 AChRs were more diffusely distributed. The functional properties of the ␣3 AChRs in tsA201 cells were characterized by whole cell patch clamp using both acetylcholine and nicotine as agonists. Nicotine was a partial agonist on ␣3␤4 AChRs and nearly a full a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
212
2
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(228 citation statements)
references
References 47 publications
10
212
2
4
Order By: Relevance
“…2). Likewise, it is probable that desensitization of the lower affinity putative ␣3␤4*-nAChRs, as observed in various cells representative of both the autonomic nervous system and CNS (Higgins and Berg, 1988;Oortigiesen and Vijverberg, 1989;Mathie et al, 1990;Khiroug et al, 1997Khiroug et al, , 1998Boyd, 1987;Ifune and Steinbach, 1993;Lester and Dani, 1995), in addition to systems designed to specifically express ␣3␤4 receptors (Cachelin and Jaggi, 1991;Hsu et al, 1996;Fenster et al, 1997;Wang et al, 1998;Xiao et al, 1998), can also be explained in terms of the two-state model, although due to the slower time course of desensitization for ␤4 subunit-containing receptors (see below), the biphasic nature may only be seen clearly during longer agonist applications (e.g., Lester and Dani, 1995). Concentration-dependent analyses of desensitization of presumed native ␣3␤4* nAChRs have estimated the affinity of the desensitized state for nicotine to be Ϸ20 -300 nM (Higgins and Berg, 1988;Lester and Dani, 1995).…”
Section: Heteromeric ␣␤* Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Likewise, it is probable that desensitization of the lower affinity putative ␣3␤4*-nAChRs, as observed in various cells representative of both the autonomic nervous system and CNS (Higgins and Berg, 1988;Oortigiesen and Vijverberg, 1989;Mathie et al, 1990;Khiroug et al, 1997Khiroug et al, , 1998Boyd, 1987;Ifune and Steinbach, 1993;Lester and Dani, 1995), in addition to systems designed to specifically express ␣3␤4 receptors (Cachelin and Jaggi, 1991;Hsu et al, 1996;Fenster et al, 1997;Wang et al, 1998;Xiao et al, 1998), can also be explained in terms of the two-state model, although due to the slower time course of desensitization for ␤4 subunit-containing receptors (see below), the biphasic nature may only be seen clearly during longer agonist applications (e.g., Lester and Dani, 1995). Concentration-dependent analyses of desensitization of presumed native ␣3␤4* nAChRs have estimated the affinity of the desensitized state for nicotine to be Ϸ20 -300 nM (Higgins and Berg, 1988;Lester and Dani, 1995).…”
Section: Heteromeric ␣␤* Receptorsmentioning
confidence: 99%
“…Following on from the work of Cachelin and Jaggi (1991), several studies have suggested that the ␤ subunit (␤4/␤2) strongly influences the rate of onset of desensitization: receptors containing ␤2 subunits desensitize faster than those containing ␤4 subunits (Hsu et al, 1995;Fenster et al, 1997;Wang et al, 1998;Bohler et al, 2001). The difference is effectively due to an altered balance of the fast and slow desensitization components: Ͼ90% desensitization for ␤4*nAChRs is slow; Ͼ90% desensitization for ␤2*nAChRs is fast ( Fig.…”
Section: Heteromeric ␣␤* Receptorsmentioning
confidence: 99%
“…SH-SY5Y cells were grown in Ham's F12/MEM (v/v) supplemented with 10% fetal bovine serum, 1% antibiotics (penicillin, streptomycin) and 1% non-essential amino acids. Except for ha7-GH 4 C 1 , nicotine (100 mM-1 mM) was added into the culture medium and the cells were incubated for 24-48 h before harvesting in order to upregulate n-AChR expression (Wang et al, 1998). All cell lines were grown at 371C in a humidified atmosphere containing 5% CO 2 .…”
Section: Cell Linesmentioning
confidence: 99%
“…Upregulation of other receptor subtypes can occur with higher nicotine concentrations in some cells (e.g., Schwartz and Kenneth, 1985;Rogers and Wonnacott, 1997;Molinari et al, 1998). Nicotinic receptor upregulation has previously been reported to involve an increase in the number of receptors, but this is not associated with changes in mRNA and is thought to reflect increased assembly (Olale et al, 1997;Wang et al, 1998). Recent studies suggest that the increased binding following upregulation may reflect a change in receptor state rather than receptor number (W. Green personal communication).…”
Section: Nicotinic Receptor Upregulationmentioning
confidence: 99%